2014
DOI: 10.1002/anie.201403542
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis and Stereochemical Reassignment of Mandelalide A

Abstract: The total synthesis of the tunicate metabolite mandelalide A and the correction of its originally assigned stereochemistry are reported. Key features of the convergent, fully stereocontrolled route include the use of a Prins cyclization for the diastereoselective construction of the tetrahydropyran subunit, Rychnovsky-Bartlett cyclization for the preparation of the tetrahydrofuran moiety, Suzuki coupling, Horner-Wadsworth-Emmons macrocyclization, and glycosylation to append the L-rhamnose-derived pyranoside.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 41 publications
5
78
2
Order By: Relevance
“…However, previously, we used molecular mechanics conformational searches, quantum mechanical NMR chemical shift predictions, and DP4 analyses to support revised absolute structures of 1–4 , 13 with 1 being used as a reference model after its earlier revision by total synthesis. 5 Thus, we propose the absolute configuration of the macrocycle in 6 as shown. The relative configuration of the new butyrylated keto-sugar in 6 , formally 5-(butyryloxy)-2-hydroxy-3-methoxy-6-methyl-4-oxotetrahydro-2H-pyran, can be proposed from homonuclear coupling constants and ROESY correlations.…”
Section: Resultsmentioning
confidence: 99%
“…However, previously, we used molecular mechanics conformational searches, quantum mechanical NMR chemical shift predictions, and DP4 analyses to support revised absolute structures of 1–4 , 13 with 1 being used as a reference model after its earlier revision by total synthesis. 5 Thus, we propose the absolute configuration of the macrocycle in 6 as shown. The relative configuration of the new butyrylated keto-sugar in 6 , formally 5-(butyryloxy)-2-hydroxy-3-methoxy-6-methyl-4-oxotetrahydro-2H-pyran, can be proposed from homonuclear coupling constants and ROESY correlations.…”
Section: Resultsmentioning
confidence: 99%
“…Then, after the total synthesis of three isomers, they found that the NMR data of 35 agreed satisfactorily well with the natural product . In the meantime, the Xu, Ye, and co‐workers, independently reached the same conclusion by finding that the upper side of the molecule was the source of the problem, with all the corresponding stereocenters inverted …”
Section: Dp4mentioning
confidence: 99%
“…Removal of the acetyl groups in 135 with NaOMe afforded jadomycins B (128) in 89% yield (3aS : 3aR ¼ 3 : 2). Similar glycosylations of aglycones 136 and 137 provided glycosides 138 and 139 (62%, a : b ¼ 5 : 1 for 136; 60%, a : b ¼ 10 : 1 for 137).…”
Section: Syntheses With Heteroaryl Thioglycosidesmentioning
confidence: 99%